ANALISIS BIAYA PADA PASIEN GANGGUAN HORMON TIROID DI RUMAH SAKIT PUSAT ANGKATAN LAUT DR. RAMELAN SURABAYA - Nabila, Muthma'innatun; Nita, Yunita; Libriansyah; Lestiono; Ridwan, Achmad (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Thyroid hormone disorders, such as hyperthyroidism and hypothyroidism, are common endocrine diseases that impose a considerable economic burden. This study aimed to analyze the components of treatment costs among outpatients with thyroid hormone disorders at RSPAL Dr. Ramelan Surabaya and to examine the relationship between patient characteristics and total treatment costs. A cross-sectional design was employed from both patient and hospital perspectives, involving 86 outpatients during the period of May to July 2025. Data on direct medical costs were obtained from the hospital billing system and out-of-pocket expenses through patient interviews, while direct non-medical and indirect costs were collected through structured interviews. The results showed that most patients were female (69 patients; 80.23%) with a mean age of 42 years, and hyperthyroidism was the most common diagnosis (n=54). The total annual cost reached IDR 1,618,002,478, with an average of IDR 18,813,982 per patient. Direct medical costs represented the largest component, with laboratory examinations accounting for the highest expenditure (an average of IDR 8,245,814 per patient per year). Statistical analysis revealed significant associations between age (p=0.007) and BPJS insurance class (p=0.049) with direct medical costs, employment status (p=0.025) with direct non-medical costs, and both age (p=0.014) and employment status (p=0.000) with indirect costs. In conclusion, the treatment costs of thyroid disorders are predominantly driven by direct medical expenses, with variations influenced by age and insurance class.